Utilization of CANVA as a Learning Media for Social Studies - Ilah Armilah; Dedy Miswar; Mona Adha, Muhammad (International Journal of Educational and Life Sciences, 2024)
The aim of this study is to explain the utilization of Canva which can be used as a learning media in Social Studies (IPS) subjects along with the stages of its creation. The research method used is a literature study. Library or library research can be interpreted as a series of activities relating to methods of collecting library data, reading and taking notes and processing research materials. Canva is a web-based graphic design tool that allows users to create digital and print images by customizing social media pages, enhancing blog posts, and creating printable materials. With the various templates provided by Canva or by designing your own, Canva can be used as a learning medium and make teaching and learning activities in class more interesting.